Can we measure catalyst efficiency in asymmetric chemical reactions? A theoretical approach - El-Fayyoumy, Shaimaa; Todd, Matthew H.; Richards, Christopher J. (Beilstein Journal of Organic Chemistry, 2009)
Small molecule asymmetric catalysts are often described as being “good” or “bad” but to date there has been no way of comparing catalyst efficiency quantitatively. We define a simple formula, Asymmetric Catalyst Efficiency (ACE), that allows for such a comparison. We propose that a catalyst is more efficient if fewer atoms are utilised to give a product in a required enantiomeric excess. We illustrate this concept by analysing several well-known asymmetric catalytic chemical reactions carried out in academic laboratories, and compare small molecule catalysts with enzymes. We conclude that ACE is a useful descriptor for the comparison of diverse catalytic systems. It is also noteworthy that, despite the relatively short period of investigation into small molecule catalysts, they are competitive with enzymes with regards to this measure of catalytic efficiency.
Keywords: asymmetric; catalysis; enzymes; organocatalysis; transition metal complexes